Tantangan Pengelolaan Sampah Berbasis Reduce, Reuse, Recycle di Kabupaten Badung - Utami, Ni Made Satya; Tarini, I G. A. Dewi; Darmada, I Wayan; Pustaka, I Gede Abdi; Putra, Nyoman A. Mustika (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: This study aims to identify and analyze problems in 3R-based waste management in Badung Regency. Research methods: This study uses a quantitative descriptive method with secondary data from the Profile of the Badung Regency Environmental Service and the Badung Central Statistics Agency (BPS) in 2024, which was carried out for four months (June–October 2024) covering 33 TPS3R locations. Findings: Badung Regency has 39 TPS 3R, with 33 actively operating and 6 not optimal. Eight TPS 3R still apply the traditional collect-transport-dispose system. The obstacles faced are weak enforcement of sanctions, inter-agency coordination, and community participation. In addition, there are obstacles to coordination between agencies as well as limitations in human resources, infrastructure, and funding. As many as 56% of TPS 3R experienced equipment damage (shredding machines, sifting), inadequate capacity, and unsuitable buildings. On the other hand, household waste sorting is low due to minimal education and incentives. Compost products are not SNI certified so they are difficult to market competitively. Implication: A strategy is needed to strengthen regulations, ongoing training, infrastructure and funding support, and cross-sector collaboration. Increasing community participation through education and incentives is also the key to the success of sustainable waste management in Badung Regency